2021
DOI: 10.1158/0008-5472.can-20-1641
|View full text |Cite
|
Sign up to set email alerts
|

MYCN-Amplified Neuroblastoma Is Addicted to Iron and Vulnerable to Inhibition of the System Xc-/Glutathione Axis

Abstract: MYCN is amplified in 20% to 25% of neuroblastoma, and MYCN-amplified neuroblastoma contributes to a large percent of pediatric cancer–related deaths. Therapy improvements for this subtype of cancer are a high priority. Here we uncover a MYCN-dependent therapeutic vulnerability in neuroblastoma. Namely, amplified MYCN rewires the cell through expression of key receptors, ultimately enhancing iron influx through increased expression of the iron import transferrin receptor 1. Accumulating iron causes reactive oxy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 50 publications
7
72
1
Order By: Relevance
“…We employed our syngeneic SK-N-SH neuroblastoma cell pair expressing exogenous MYCN or GFP [11] and performed untargeted liquid chromatography/tandem mass spectrometry of cell lysates to determine changes in a broad array of polar metabolites. Our data indicated decreased glutamate levels, increased cysteine levels and increased cysteinyl-glycine (Cys-Gly) levels, consistent with an activated system Xc-antiporter [7]. 'Confirming our previously published data from colorimetric analyses of GSH levels [7], GSH levels were increased over 5-fold in the presence of MYCN (Fig.…”
Section: Resultssupporting
confidence: 91%
“…We employed our syngeneic SK-N-SH neuroblastoma cell pair expressing exogenous MYCN or GFP [11] and performed untargeted liquid chromatography/tandem mass spectrometry of cell lysates to determine changes in a broad array of polar metabolites. Our data indicated decreased glutamate levels, increased cysteine levels and increased cysteinyl-glycine (Cys-Gly) levels, consistent with an activated system Xc-antiporter [7]. 'Confirming our previously published data from colorimetric analyses of GSH levels [7], GSH levels were increased over 5-fold in the presence of MYCN (Fig.…”
Section: Resultssupporting
confidence: 91%
“…This argument can be further supported by the study from Floros et al For instance, SAS is capable of inducing~70% cell death in MYCN-amplified NB cells. However, knockdown of two System X c (−) components SLC7A11 and SLC3A2 induce only~25% cell death in the same cell line 31 , confirming that SAS harbors considerable off-target effects. In conclusion, the complex effects of SAS treatments leading to ferroptosis cannot be solely linked to the sensitivity of NB cells to System X c (−) inhibition.…”
Section: Discussionmentioning
confidence: 88%
“…Notably, Floros et al recently reported that MYCNamplified NB cells are more sensitive to the system X c (−) inhibitor sulfasalazine (SAS) 31 . Indeed, MYCN-amplified NB cells are slightly sensitive to SAS as reflected by their smaller IC50 values compared to non-amplified cells, although no statistical significance was achieved in our hands (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In about 25% of neuroblastoma cases MYCN is amplified ( 19 ). In patient-derived xenografts of these cases, the xCT-driven antioxidant response after sulfasalazine application is increased compared to controls, which leads to an increase in ferroptosis and subsequently limited tumor growth ( 19 ).…”
Section: Promising Findings On Ferroptosis Induction In Neuroblastoma and Meningiomamentioning
confidence: 99%
“…In about 25% of neuroblastoma cases MYCN is amplified ( 19 ). In patient-derived xenografts of these cases, the xCT-driven antioxidant response after sulfasalazine application is increased compared to controls, which leads to an increase in ferroptosis and subsequently limited tumor growth ( 19 ). Further studies revealed that the transferrin receptor 1 was upregulated in response to such MYCN amplification, leading to increased GPx4 sensitivity and rendering neuroblastoma cells vulnerable to ferroptosis induction ( 20 ).…”
Section: Promising Findings On Ferroptosis Induction In Neuroblastoma and Meningiomamentioning
confidence: 99%